Pollen contaminated with a triple-action fungicide induced oxidative stress and reduced longevity though with less impact on lifespan in honey bees from well fed colonies - Alves, Thais R.R. [UNESP]; Trivellato, Matheus F. [UNESP]; Freitas, Tainá A.L. [UNESP]; Kato, Aline Y. [UNESP]; Gomes, Cássia R.A. [UNESP]; Ferraz, Yara M.M. [UNESP]; Serafim, Jéssica A. [UNESP]; De Jong, David; Prado, Evandro P. [UNESP]; Vicente, Eduardo F. [UNESP]; Orsi, Ricardo O. [UNESP]; Pereira, Gener T.; et al. (Elsevier, 2024)
Experiments were conducted to determine the effects of a triple-action fungicide on bees and whether improved nutrition can ameliorate eventual negative impacts. In cage tests, newly-emerged bees from well fed and from nutritionally-restricted honey bee colonies were fed for five days with pollen from sunflowers that had been sprayed or not with a commercial fungicide containing bixafen, prothioconazole and trifloxystrobin. Bees from well-fed colonies were significantly larger and consumed more uncontaminated pollen. They also exhibited increased glutathione peroxidase activity and higher concentrations of pyridine nucleotides, both of which are involved in antioxidase defense. However, pollen contaminated with fungicide led to an increase in lipoperoxidation, regardless of nutritional status. Bee longevity was reduced by both fungicide contamination of the pollen diet and poor nutritional condition. The fungicide adversely affected bees fed with contaminated pollen, though nutritional supplementation of the bee colonies that reared the bees partially compensated for these effects.
Keywords: Bixafen; Nutrition; Prothioconazole; Redox; Trifloxystrobin